2020
DOI: 10.1515/dx-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical biomarkers alterations in Coronavirus Disease 2019 (COVID-19)

Abstract: AbstractCoronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a respiratory disease, which can evolve into multi-organ failure (MOF), leading to death. Several biochemical alterations have been described in COVID-19 patients. To date, many biomarkers reflecting the main pathophysiological characteristics of the disease have been identified and associated with the risk of developing severe disease. Lymphopenia represents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 67 publications
4
84
0
8
Order By: Relevance
“…After two to three weeks of hospitalization, AST, GGT and ALP began to rise and were often higher in the ICU group than in the non-ICU group. Indeed, specific liver enzymes appear to be a late biomarker of organ damage as multiples studies showed [10,18,24]. In this study AST rose until the second week of hospitalization.…”
Section: Late Biomarkers Of Covid-19mentioning
confidence: 49%
See 1 more Smart Citation
“…After two to three weeks of hospitalization, AST, GGT and ALP began to rise and were often higher in the ICU group than in the non-ICU group. Indeed, specific liver enzymes appear to be a late biomarker of organ damage as multiples studies showed [10,18,24]. In this study AST rose until the second week of hospitalization.…”
Section: Late Biomarkers Of Covid-19mentioning
confidence: 49%
“…The responsible mechanisms are still unknown, but the main hypotheses are either chemokine-mediated lymphocyte redistribution and sequestration in the lungs or bone marrow suppression via CD13 or CD66 [14][15][16][17]. Lymphopenia, appearing generally 8 days after the onset of symptoms, was frequent and more pronounced within the first week of hospitalization and continued right until the third week of hospitalization [18]. In order to determine its prognostic usefulness, we compared the lymphocyte values found in different patients' groups.…”
Section: Early Biomarkers Of Covid-19mentioning
confidence: 99%
“…Possible mechanisms implicated in these neurological conditions are neuronal injury associated with direct virus infection, hyperinflammation syndrome associated with cytokines storm, a para- or post-infectious inflammatory disease, an immune-mediated disease, or a secondary process due to severe effects of a systemic disorder (sepsis, hyperpyrexia, hypoxia, hypercoagulability, critical illness) ( Gris et al, 2020 , Mehta et al, 2020b , Zubair et al, 2020 ). Several biomarkers for COVID-19 severity have been identified in blood, including C-reactive protein, D-dimer, lactate dehydrogenase, interleukin-6, and ferritin ( Ciaccio and Agnello 2020 ), but less evidences are available for cerebrospinal fluid (CSF) biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 17 months of its spread, till 30 th April 2021, approximately 152,113,053 positive cases and 3,196,373 deaths were reported worldwide owing to the high transmission efficiency of SARS-CoV-2 [2]. Coronaviruses (CoVs) are single stranded RNA viruses classified into four genera: alpha-, beta-, gamma-and delta-CoV ; SARS-CoV-2 is a β-COV [3]. COVID-19 primarily manifested as a respiratory tract infection with symptoms of fever, dry cough and fatigue; in severer cases, dyspnea and may also manifest as systemic infection.…”
Section: Introductionmentioning
confidence: 99%